2004
DOI: 10.1158/0008-5472.can-03-3998
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 27 Increases after Androgen Ablation and Plays a Cytoprotective Role in Hormone-Refractory Prostate Cancer

Abstract: Heat shock protein 27 (Hsp27) is a chaperone implicated as an independent predictor of clinical outcome in prostate cancer. Our aim was to characterize changes in Hsp27 after androgen withdrawal and during androgen-independent progression in prostate xenografts and human prostate cancer to assess the functional significance of these changes using antisense inhibition of Hsp27. A tissue microarray was used to measure changes in Hsp27 protein expression in 232 specimens from hormone naive and posthormone-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
271
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 290 publications
(292 citation statements)
references
References 41 publications
14
271
2
1
Order By: Relevance
“…43 Hsp27 has been reported to be elevated in many human tumors and is a predictor of poor clinical outcome (androgen-independence), as it has a cytoprotective role by interfering with many key regulators of apoptosis. 37,44 Multiple RTKs, Bcl-2 and Hsp27 have all been implicated in hormone resistance, 41,45,46 and we have shown that Reg IV modulates the spectrum, therefore suggesting that a Reg IVtargeted therapy could have utility in drug resistant patient populations. In addition to expanding our understanding of signaling downstream of Reg IV, our results support a potential therapeutic benefit in neutralizing Reg IV activity in Reg IV-positive patient populations.…”
Section: Cancer Cell Biologymentioning
confidence: 84%
See 1 more Smart Citation
“…43 Hsp27 has been reported to be elevated in many human tumors and is a predictor of poor clinical outcome (androgen-independence), as it has a cytoprotective role by interfering with many key regulators of apoptosis. 37,44 Multiple RTKs, Bcl-2 and Hsp27 have all been implicated in hormone resistance, 41,45,46 and we have shown that Reg IV modulates the spectrum, therefore suggesting that a Reg IVtargeted therapy could have utility in drug resistant patient populations. In addition to expanding our understanding of signaling downstream of Reg IV, our results support a potential therapeutic benefit in neutralizing Reg IV activity in Reg IV-positive patient populations.…”
Section: Cancer Cell Biologymentioning
confidence: 84%
“…35 In addition, the expression of IGF-1, which signals through IGF1R and IR, has been correlated with an elevated risk of developing prostate cancer, 36 and IGF-1 signaling has been implicated in resistance to both general cytotoxic treatment regimens and to targeted therapies. 37 While the mechanism by which Reg IV is impacting these RTKs is not clear, it is of note that RTKs physically interact with each other (e.g., EGFR and…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoresis, hybridization, and washing conditions were carried out as reported previously (18,23). Human Hsp27 cDNA probe was obtained from StressGen (Victoria, BC, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Antisense oligonucleotides (ASO) are powerful tools that specifically hybridize with complementary mRNA regions to form RNA/DNA duplexes to inhibit target gene expression in a sequencespecific manner. Several ASOs targeting genes involved in neoplastic progression have been evaluated as potential therapeutic agents (17,18). In fact, the combined use of ASO with other compounds, such as chemotherapeutic agents, has shown synergistic antineoplastic effects in several tumor models (18,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation